ANALISIS MODAL KERJA DAN LIKUIDITAS UNTUK MENINGKATKAN PROFITABILITAS PADA PT KARYA MURNI PERKASA MEDAN - Ilham Sonata; Seri Ramadhani (JRAM (Jurnal Riset Akuntansi Multiparadigma), 2021)
This study aims to determine working capital turnover and liquidity on profitability in 2018-2019 at PT. Karya Murni Perkasa Medan. The type of data used is secondary data, the data has been processed and obtained from sources that have been documented in the company including financial statements for 2018 and 2016 as well as company history and the data analysis technique used is by using descriptive methods, namely methods using data compiled, interpreted and analyzed so as to provide a clear and complete picture for solving the problems encountered. Based on the financial statements in the form of a statement of financial position and income statement, analyzed using financial ratios. Based on the results of research and discussion, it can be concluded that Working Capital as a whole can be said to be less good, because Working Capital Turnover has decreased from 2018-2019. Liquidity, measured by using the current ratio, quick ratio and cash ratio shows that the company's condition is in good condition, but when compared to the industry average standard, the liquidity ratio in 2018-2019 is declared not good because it is below the average. Financial performance PT. Karya Murni Perkasa in terms of profitability shows the company's financial condition, it is known that net profit margin, return on assets and return on equity have the same ratio level, namely a decrease in each ratio in 2018-2019 and when compared to the industry average standard, each ratio in 2018-2019 is not good because it is still below the average.